Mapping clinical and imaging factors that might predict cardiac events in breast cancer patients - Otero-Pla, Eugenia; Fuentes Raspall, Maria Josefa; Gallego Franco, Pedro; Fernández Martínez, Juan; Gich Saladich, Ignasi; Jornet Sala, Nuria; Lizondo Gisbert, Maria; Rojas Cordero, Jady; Isern Verdum, Josep; Sancho-Pardo, Gemma (Frontiers in Oncology, 2025)
BackgroundBreast cancer is the most common in women, with a 90% overall survival at 5 years. Cardiotoxicity is a side effect that can modify their morbidity and mortality. Its low prevalence and long latency period have challenged the establishment of a strategy for early detection and prevention.ObjectivesTo investigate the association between coronary artery calcium (CAC) in planning computed tomography (CT) and cardiac events.MethodsRetrospective cohort of 873 breast cancer patients (460 right-side; 413 left-side) treated with radiotherapy (2013-2022). We extract the Hounsfield Unit to quantify the CAC degree from the heart structure in the planning CT. We used IBM-SPSS software (V 29.0 Armonk, NY) for the statistical analysis.ResultsAfter a median follow-up of 4.52 years (range: 2.42-6.22 years), the cardiac events incidence was 1.95% vs 5.1% in right and left breast cancer, respectively. The mean heart dose was higher in cases with cardiac events (6.74Gy vs 2.28Gy; p<0.01). CAC score>0 was detected in 32.76% of planning CT and was more frequent in the elderly and those with cardiovascular risk factors (p<0.01). Patients with cardiac events presented a CAC score>0 in 41.4% of cases. However, the overall survival in these patients did not differ from those without CAC (p=0.58).ConclusionsPatients with cardiovascular risk factors and a mean cardiac dose greater than 5 Gy are at increased risk of cardiotoxicity and should be referred for Cardio-Oncology evaluation. The application of the CAC score in CT planning could be a valuable screening test that requires further study.